2022
DOI: 10.1163/15691497-12341622
|View full text |Cite
|
Sign up to set email alerts
|

Non-Inclusive Trade Unionism in the Tea Estates in Assam

Abstract: The state of Assam alone produces nearly 53 percent of the total tea production in India. Around one million workers are engaged in the tea industry in India. Tea – as a commercial product first cultivated and expanded by the British – is an outcome of the toil and struggle of the Adivasi workers or indigenous people of central and east India who were made to migrate to Assam under extremely brutal conditions, and they form one of the most oppressed communities in the state. This section of the population has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Engagement of women's labour is higher in tea plantations because of their gendered attributes to the task of plucking tea leaves in particular and for maintaining a steady social reproduction of labour. Duara and Mallick (2019) have found that sexual division of labour, patriarchy, sexual abuse and gender and class intersectionality are the reasons for the marginalisation of women workers in the tea estates of Assam. The negligible role of the state and poor standard of social security and welfare measures are responsible for the poor working and health conditions of the women workers.…”
Section: Women Workers In the Tea Plantation Industrymentioning
confidence: 99%
“…Engagement of women's labour is higher in tea plantations because of their gendered attributes to the task of plucking tea leaves in particular and for maintaining a steady social reproduction of labour. Duara and Mallick (2019) have found that sexual division of labour, patriarchy, sexual abuse and gender and class intersectionality are the reasons for the marginalisation of women workers in the tea estates of Assam. The negligible role of the state and poor standard of social security and welfare measures are responsible for the poor working and health conditions of the women workers.…”
Section: Women Workers In the Tea Plantation Industrymentioning
confidence: 99%
“…Then Britishers decided to bring laborers from different parts of the country, mainly from the newly formed Chotta Nagpur princely state of British India, which covered many parts of Jharkhand, Bihar, Chhattisgarh, Odisha and West Bengal states of India (Bhowmik, 2011; Das, 2016). At that time, people were convinced to migrate due to their state of poverty and lack of occupational sources in their home state (Duara and Mallick, 2012); and Britishers promised to give land for housing and cultivation, which in turn transformed them into full-fledged proletarians in later years (Chattopadhyay, 1988).…”
Section: Context Of the Studymentioning
confidence: 99%
“…The Act also mentioned provisions of ration at nominal rates to all workers as part of their wages. It clearly specifies that provisions such as housing facility, medical facility and maternity allowances must be available for every worker; however, the temporary ( faltu ) workers do not entitled to any of these benefits except ration at nominal rates (Bhowmik, 2015b; Duara and Mallick, 2012), that too only for few months in a year when they get work. Successive governments in the state also have failed to force employers to implement the Act as employers always argue that due to lower auction prices after 1990, the tea industry is going through massive crises (Das, 2022; Misra, 2003).…”
Section: Context Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…4 The PLA was meant to provide some restitution as well as assure better working conditions for workers in the plantations in an effort to reverse the indignities of their indentured past. However, rather than reduce the gap between the management and workers, the trade unions for a variety of complex reasons chose to side with the management rather than the workers (Duara, 2017). From personal experience growing up in the industry in the 1980s, we were aware that some tea companies offered extraordinary benefits for a small section of managerial executives.…”
Section: Tea: Coloniser's Gateway Cropmentioning
confidence: 99%